Antibacterial Activity of Bacillus spp. Against Foodborne Pathogens - แก้วอ่อน, สายใจ (YRU Journal of Science and Technology, 2018)
The aim of this research was to study the antibacterial activity of Bacillus amyloliquefaciens B17, Bacillus amyloliquefaciens B19, Bacillus pumilus B21 and Bacillus subtilis B25 against 5 species of foodborne pathogen including Staphylococcus aureus TISTR 118, Escherichia coli O157:H7, Escherichia coli ATCC 8739, Salmonella typhimurium TISTR 292 and Salmonella Typhimurium S003. Of four Bacillus strains, B. amyloliquefaciens B19 showed the potential antibacterial activity against E. coli ATCC 8439, E. coli 0157:H7, S. aureus TISTR 118 and Salmonella Typhimurium TISTR 292 by agar spot diffusion. The highest antibacterial activity was shown against E. coli 0157:H7 and S. aureus TISTR 118. B. amyloliquefaciens B19 inhibited the growth of E. coli 0157:H7 and S. aureus TISTR 118 with the inhibition zones of 28.70±0.60 and 25.40±0.94 mm, respectively by agar well diffusion. The Minimum inhibitory concentration (MIC) of B. amyloliquefaciens B19 against E. coli 0157:H7 was 10 4 cfu/ml with inhibition zone of 11.50±0.00 mm while the MIC against S. aureus TISTR 118 was 10 6 cfu/ml with inhibition zone of 16.20±1.77 mm. Furthermore, B. amyloliquefaciens B19 was tested for red blood cell hydrolysis. The result showed that it could not hydrolyze the sheep red blood cell. These results suggested that B. amyloliquefaciens could be used for foodborne pathogen control.